PENGARUH BAURAN PEMASARAN (4P) TERHADAP KEPUTUSANPEMBELIAN PERUMAHAN PT. BERLIAN BERSAUDARA PROPERTINDO (Studi Kasus Perumahan Taman Arizona 1 Taman Arizona 2 dan Taman Arizona 3 di Talang Jambi Palembang) - Noevie Susanti; Hamid Halin; M. Kurniawan (Jurnal Ilmiah Ekonomi Global Masa Kini)
As many corporate institutions use the concept of marketing mix as a strategy to attract potential customers to be able to improve consumer purchasing decisions. This study aims to determine and test the effect of Marketing Mix on Purchasing Decision at PT. Berlian Bersaudara Propertindo Palembang. By using quantitative statistical research methods and data analysis techniques used are simple regression analysis. Population in this research is consumer who buy house at PT. Berlian Bersaudara Propertindo Palembang and sample of 134 respondents with sampling technique using Slovin method.Instrument validity test results show that rcount ≥ rtabel means that all valid items and reliability is above 0.70 means all reliable. When viewed based on Test t shows the value of tcount (10,620) ≥ ttabel (1,656) sig (0,000) ≥ 0.05. It shows that the Marketing Mix is a significant effect on Purchase Decision. From the correlation result show the correlation between Marketing Mix to Decision of Purchase high assumption that is equal to 67,9%. Then the coefficient of determination (R2) shows the amount of 0.461% of the Marketing Mix of Purchase Decision, while the remaining 53.9% influenced by other variables not examined in this study.Keywords : Marketing mix, Purchase Decision, Quantitative Methods.